NEW KAZAKH LETTER BASED ON THE LATIN CHART - Bazarbayeva Zeinep Muslimovna (Scientific Journal of Pedagogy and Economics, 2019)
The article considers the most acceptable ways of transition of the Kazakh alphabet to the Latin script. The principles of the new Kazakh letter are analyzed on the basis of a new spelling that establishes the correct spelling of phonemes, morphemes, words based on three basic principles: traditional-historical, phonetic and phonemic (morphological).The essence of the principle of economy in the new Latinized Kazakh letter is revealed. The basic principles of the theory of writing are described. The advantage of the phonemic principle in Kazakh orthography is revealed, in which the same letters of the alphabet designate the phoneme in all its mutations, no matter how it sounds. The law of phonology and its influence on the development and formation of the Kazakh phonetic system are described. The external and internal factors of the origin of new phonemes and their designation on the letter are described. The formation of new phonemes is associated with the development of language and thinking, supplementing it with new concepts, new vocabulary, the influence of adjacent cultures and civilizations. With frequent use, borrowed sounds adapt to the articulatory apparatus of its carriers and the phonetic system of the language is enriched with new phonemes. The rules of spelling and pronunciation of words in a new Latinized Kazakh letter are analyzed.